Cooperatives, mutuals and local development policies:: an approach to the associative fabric of the province of Santa Fe, Argentina - Carini, Gabriel Fernando; Frutero Llull, Román; Riberi, Laura (Cooperativismo & Desarrollo, 2022)
The objective of this article is to describe the first results of the survey of cooperatives and mutuals in the province of Santa Fe, Argentina, carried out within the framework of the Observatorio del Ecosistema Asociativo of said territory. In this sense, it not only seeks to narrate the experience on the structuring of this body and specify the methodological aspects involved to monitor the associative phenomenon but, fundamentally, it seeks to provide a synthesis of the main features assumed by the dynamics of cooperatives and mutual their distribution in the territory, the diversity of social objects and some continuities and ruptures in their historical evolution.